Pengaruh Brand Ambassador, Electronic Word Of Mouth (E-Wom), dan Persepsi Harga terhadap Keputusan Pembelian pada E- Commerce Tokopedia: Survey Pada Mahasiswa Fakultas Ekonomi dan Bisnis UNISRI - Kalyana Risma Ananta; Adcharina Pratiwi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research was conducted on students of the Faculty of Economics and Business at Slamet Riyadi University in Surakarta who use the e-commerce platform Tokopedia. The purpose of this study is to analyze the significance of the influence of brand ambassadors, electronic word of mouth (e-WOM), and price perception on purchasing decisions in Tokopedia's e-commerce. The type of data used is quantitative data, with primary data sources employed in this research. The data analysis techniques used in this study include multiple linear regression analysis, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results of the multiple linear regression analysis from this study are represented by the equation Y = 6.518 + 0.695 X1 + 0.168 X2 - 0.210 X3 + e. The t-test results indicate that the variables of brand ambassador, electronic word of mouth (e-WOM), and price perception have a significant effect on purchasing decisions in Tokopedia's e-commerce. The F-test results show that the model is appropriate for predicting the influence of brand ambassadors, electronic word of mouth (e-WOM), and price perception on purchasing decisions in Tokopedia's e-commerce. The coefficient of determination (R²) obtained is 0.594, meaning that the independent variables X1 (brand ambassador), X2 (electronic word of mouth (e-WOM)), and X3 (price perception) contribute 59.4% to Y (purchasing decisions). The remaining 40.6% (100% - 59.4%) is explained by other variables not included in this study.